THE RELATIONSHIP BETWEEN CHARACTERISTICS OF PREGNANT WOMEN WITH HYPERTENSION AND THEIR HEALTHY LIFESTYLE - Florisma Arista Riti Tegu; Yosi Maria Wijaya; Maria Yunita Indriarini (Journal of Maternity Care and Reproductive Health, 2021)
Hypertension in pregnancy can be prevented by controlling the healthy lifestyle. However, the majority of research on this topic has been conducted on lifestyle in women with normal pregnancy. Few studies of lifestyle have focused on Indonesian pregnant women with hypertension. The purpose of this study is to determine the association of demographic characteristics and the lifestyle of pregnant women who have hypertension. This research method is cross-sectional study, 76 of women with hypertension during pregnancy were recruited from primary health care, West Java, Indonesia. Inclusion criteria were gestational age ≥ 28 weeks with the blood pressure systole ≥ 140 mmHg and diastole ≥ 90 mmHg. Data were collected using two instruments: demographic data and the Health Promoting Life Style Profile (HPLP II). Data were analyzed using the descriptive statistic approach and the Chi-square test. Results: Bivariate analysis using Chi-square test shows education (p-value 0,021), occupation (p-value 0,025) and income (p-value 0,023) are the factors related to lifestyle among pregnant woman who have hypertension. Conclusion. Understanding the lifestyle and associated factors contributes to health care providers’ ability to design effective interventions intended to improve healthy lifestyle among pregnant women with hypertension.